Genetic diversity and paternity of Brycon orbignyanus offspring obtained for different reproductive systems - Lopera-Barrero, Nelson Mauricio; Alvarez, Camilo Andres Reyes; Rodriguez-Rodriguez, Maria del Pilar; Povh, Jayme Aparecido; Vargas, Lauro; Streit Júnior, Danilo Pedro; Sirol, Rodolfo Nardes; Ribeiro, Ricardo Pereira (Semina: Ciências Agrárias, 2014)
The objective of this study was to estimate the genetic diversity and the paternity of Brycon orbignyanus offspring's obtained with the extrusion and semi-natural reproductive systems, by microsatellites markers. The four loci used produced 11 alleles, being observed three alleles (BoM1, BoM5 and BoM7) and two alleles (BoM2) for locus present in the parental and in the offspring of both reproductive systems. In the offspring of the extrusion system low frequency alleles was observed for the locus BoM5 (allele B = 0.095) and BoM7 (allele C = 0.059) and there was a decrease of genetic variability (observe heterozygosity-Ho = 0.900 and 0.823; Shannon index-IS = 0.937 and 0.886; Nei genetic diversity-DGN = 0.604 and 0.566, respectively). For the offspring of the semi-natural system the allele frequencies stayed stable being verified an unequal frequency for each locus. The genetic variability in the offspring was preserved, being corroborated by the Ho values (0.975 and 0.945), IS (0.927 and 0.924) and DGN (0.593 and 0.581) for parental and offspring, respectively. Deviations were observed (P <0.01) in the Hardy-Weinberg equilibrium and linkage disequilibrium for the two reproductive systems. The inbreeding coefficient (Fis) it showed deficit of heterozygote in the offspring of the extrusion system. Multiple paternity and differed reproductive contributions in the composition of the families in the offspring in the two reproductive systems was observed, with the presence of reproductive dominance in the semi-natural system.